2014
DOI: 10.1111/bph.12960
|View full text |Cite
|
Sign up to set email alerts
|

CardiacNOsignalling in the metabolic syndrome

Abstract: It is well documented that metabolic syndrome (i.e. a group of risk factors, such as abdominal obesity, elevated blood pressure, elevated fasting plasma glucose, high serum triglycerides and low cholesterol level in high-density lipoprotein), which raises the risk for heart disease and diabetes, is associated with increased reactive oxygen and nitrogen species (ROS/RNS) generation. ROS/RNS can modulate cardiac NO signalling and trigger various adaptive changes in NOS and antioxidant enzyme expressions/activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 215 publications
(239 reference statements)
2
42
0
1
Order By: Relevance
“…The literature shows that the level of endogenously formed ONOO − increases in adipose tissue mainly as a result of hyperglycaemia, that is, established diabetes (Koeck et al , ). A similar increase in the ONOO − level in diabetic hearts has been reported (Pechánová et al , ; Varga et al , ). In these circumstances, increased signalling through advanced glycation end products or their corresponding receptors (RAGE) may additionally lead to excessive superoxide formation and ONOO − increase.…”
Section: Introductionsupporting
confidence: 85%
“…The literature shows that the level of endogenously formed ONOO − increases in adipose tissue mainly as a result of hyperglycaemia, that is, established diabetes (Koeck et al , ). A similar increase in the ONOO − level in diabetic hearts has been reported (Pechánová et al , ; Varga et al , ). In these circumstances, increased signalling through advanced glycation end products or their corresponding receptors (RAGE) may additionally lead to excessive superoxide formation and ONOO − increase.…”
Section: Introductionsupporting
confidence: 85%
“…We found that NOS1, an enzyme generating NO, a major modulator of cardiac function and calcium fluxes (Pechanova et al , ), was highly upregulated specifically in the GRAC heart, and this was to large extent prevented in GROX hearts. NOS1 and NOS3 upregulation was accompanied by changes in NO‐ and Ca 2+ channel‐related gene expression, both alleviated by AOX.…”
Section: Discussionmentioning
confidence: 85%
“…Preclinical studies have demonstrated a variety of protective effects in animal models of cardiovascular disease, including hypertension (Mizutani et al , ; Dolinsky et al , ; Dolinsky et al , ), hypercholesterolaemia (Penumathsa et al , ; Juhasz et al , ), atherosclerosis (Wang et al , ; Do et al , ), ischaemic heart disease (Andreadou et al , ; Novelle et al , ), diabetes (Su et al , ; Um et al , ) and metabolic syndrome (Novelle et al , ; Pechanova et al , ). These cardiovascular effects of resveratrol in laboratory animals have been reviewed in our previous article (Li et al , ) and in a recent publication (Zordoky et al , ).…”
Section: Cardiovascular Effects Of Resveratrol In Humansmentioning
confidence: 99%